2019
DOI: 10.1038/s41598-019-46515-y
|View full text |Cite
|
Sign up to set email alerts
|

Sub-threshold micropulse laser treatment reduces inflammatory biomarkers in aqueous humour of diabetic patients with macular edema

Abstract: Subthreshold micropulse laser (SMPL) is a tissue-sparing technique whose efficacy is demonstrated for diabetic macular edema (DME) treatment. However, its mechanism of action is poorly known. A prospective observational study was performed on naïve DME patients treated with SMPL, to evaluate the changes of aqueous humor (AH) inflammatory and vaso-active biomarkers after treatments. AH samples of eighteen DME eyes were collected before and after SMPL. Ten non-diabetic AH samples served as controls. Full ophthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…1,2,17,18 Recently, it has been reported that SMPL reduces the aqueous humour (AH) concentration of inflammatory cytokines secreted by retinal glial cells (GLCs), both Müller cells (MCs) and microglial cells (MGCs) in eyes with DME. 19,20 A decrease in the inner nuclear layer thickness (INL), where the bodies of MCs are located, was reported after SMPL. 21 Whether this effect on GLCs is direct or mediated by the RPE has still to be evaluated and confirmed; however, these findings suggest that SMPL might be able to downregulate the inflammatory retinal processes activated by hyperglycemia in diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,17,18 Recently, it has been reported that SMPL reduces the aqueous humour (AH) concentration of inflammatory cytokines secreted by retinal glial cells (GLCs), both Müller cells (MCs) and microglial cells (MGCs) in eyes with DME. 19,20 A decrease in the inner nuclear layer thickness (INL), where the bodies of MCs are located, was reported after SMPL. 21 Whether this effect on GLCs is direct or mediated by the RPE has still to be evaluated and confirmed; however, these findings suggest that SMPL might be able to downregulate the inflammatory retinal processes activated by hyperglycemia in diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%
“…21 Whether this effect on GLCs is direct or mediated by the RPE has still to be evaluated and confirmed; however, these findings suggest that SMPL might be able to downregulate the inflammatory retinal processes activated by hyperglycemia in diabetes mellitus (DM). 19,20 The clinical effects of SMPL on the retina in eyes with DME have been evaluated using standard imaging techniques, such as color fundus photography, optical coherence tomography (OCT), fundus autofluorescence (FAF), fluorescein angiography (FFA), and microperimetry. 3,4,[9][10][11]15 However, only one study reported on the use of OCT angiography (OCTA) in evaluating microvascular changes occurring after SMPL treatment in DME.…”
Section: Introductionmentioning
confidence: 99%
“…It is the size of the device (in this case the catalytic reaction and cascade of effects initiated by HSP activation) and not the fuse that matters. [8][9][10][11][12][13][14][15]37,38,42,[47][48][49][50] Because exceeding the threshold for HSP activation does not increase HSP activation but increases the risk of thermal cell death and retinal damage, laser parameters exceeding this threshold ( HSP = 1) should be avoided. Because of the catalytic response to laser HSP activation, treatment parameters with an HSP < 1.0 can also be used to increase treatment safety, without compromising efficacy ( Supplementary Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these well-recognized and long-accepted drawbacks, LIRD is not known to have any intrinsic or direct therapeutic effects; these arising instead from cells affected, but not killed, by laser application. [5][6][7][8][9][10][11][12][13][14][15] Defining photocoagulation, and indeed any degree of LIRD, as complications rather than goals of treatment, modern retinal laser therapy seeks to maximize both treatment safety and efficacy and broaden treatment indications by precluding LIRD. 2,7, The cornerstones of modern retinal laser therapy were established and defined by low-intensity/highdensity subthreshold diode (810 nm) micropulse laser (SDM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation